Effect of Oxygen and Hydrogen Peroxide on the Photocatalytic Degradation of Monochlorobenzene in Aqueous Suspension - Dyi-Hwa Tseng; Lain-Chuen Juang; Hsin-Hsu Huang (International Journal of Photoenergy)
The influences of oxygen and hydrogen peroxide () on the degradation and mineralization of monochlorobenzene (MCB) during UV/ process were investigated. Experimental results indicated that oxygen was a determining parameter for promoting the photocatalytic degradation. The presence of oxygen reduced the illumination time needed for the complete decay of MCB from 240 to 120 min. The photocatalytic degradation of MCB in UV// photocatalysis followed a simplified two-step consecutive kinetics. The rate constants of degradation () and mineralization () were increased from 0.016 to 0.046 min−1 and from 0.001 to 0.006 min−1, respectively, as the initial concentration of dissolved oxygen (DO) was increased from 1.6 to 28.3 mg L−1. Owing to the fact that acted as an electron and hydroxyl radicals () scavenger, the addition of should in a proper dosage range to enhance the degradation and mineralization of MCB. The optimal dosage for MCB degradation was 22.5 mg L−1, whereas the most efficient dosage for MCB mineralization was 45.0 mg L−1. In order to minimize the adverse effects of higher dosage, including the capture of radicals and competitive adsorption, and to improve the photocatalytic degradation of MCB, the sequential replenishment of was suggested. For the stepwise addition of a total dosage of 45.0 mg L−1, a complete destruction of MCB was observed within 120 min of irradiation. Additionally, the mineralization efficiency was about 87.4% after 240 min of illumination time.